2014
DOI: 10.9738/intsurg-d-14-00063.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Frequencies of Abdominal Wall Hernias and the Preferences for Their Repair: A Multicenter National Study From Turkey

Abstract: Abdominal wall hernias are a common problem in the general population. A Western estimate reveals that the lifetime risk of developing a hernia is about 2%.1–3 As a result, hernia repairs likely comprise the most frequent general surgery operations. More than 20 million hernias are estimated to be repaired every year around the world.4 Numerous repair techniques have been described to date however tension-free mesh repairs are widely used today because of their low hernia recurrence rates. Nevertheless, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
9
3
Order By: Relevance
“…9 Among hernias, inguinal hernia surgeries are the ones which were frequently performed in our study, a finding consistent with many other studies. [3][4][5]7,9,10 Though inguinal hernia surgeries were the commonest procedures, their rate has decreased by 15.4% from 2009 to 2018 in our study which is consistent with Serker et al and Dabbas et al findings, where they have observed a decrease in 7.9% over 5 years from 2005 to 2010 and 11.6% over 10 years from 1998 to 2008 respectively. 9,10 In the current era, the rate of incisional hernia surgeries is on a significant rise.…”
Section: Spectrum Of Surgeriessupporting
confidence: 92%
See 1 more Smart Citation
“…9 Among hernias, inguinal hernia surgeries are the ones which were frequently performed in our study, a finding consistent with many other studies. [3][4][5]7,9,10 Though inguinal hernia surgeries were the commonest procedures, their rate has decreased by 15.4% from 2009 to 2018 in our study which is consistent with Serker et al and Dabbas et al findings, where they have observed a decrease in 7.9% over 5 years from 2005 to 2010 and 11.6% over 10 years from 1998 to 2008 respectively. 9,10 In the current era, the rate of incisional hernia surgeries is on a significant rise.…”
Section: Spectrum Of Surgeriessupporting
confidence: 92%
“…Due to an increase in the number of laparotomies, the rate of incisional hernia surgeries has increased over time. 9,10 In our study, we included incisional hernias in ventral hernias which showed a significant increase.…”
Section: Spectrum Of Surgeriesmentioning
confidence: 99%
“…The number of papers on inguinal hernias were more than three times of those about incisional hernias. This is somewhat expected given the fact that inguinal hernia repairs comprise the majority of operations for abdominal wall hernias (21,22). However, incisional hernia articles had a higher mean number of citations than papers on inguinal hernias.…”
Section: Discussionmentioning
confidence: 90%
“…An abdominal wall hernia is defined as a defect in the continuity of fascial and/or muscle-aponeurotic structures, allowing the protrusion or exit of elements that normally do not pass through them; In order of frequency depending on their location are inguinal hernia (70-75%), femoral hernia (6-17%), umbilical hernia (3-8.5%), and other less common forms (1-2%). 1,2 The hernias of the inguinal region are classified by anatomy in femoral and inguinal, the latter being subdivided into direct and indirect hernias, according to their medial or lateral relationship to the lower epigastric vessels respectively. The indirect inguinal hernia protrudes through the internal inguinal ring along with the cremastomeric fascia and extends downwards over the spermatic cord, may be limited to the groin area or spread through the outer inguinal ring and descend to the level of the testicles.…”
Section: Introductionmentioning
confidence: 99%